Impact of an oblique breaking wave on a wall - Shu, Jian Jun (2011)
The intention of this paper is to study impact force of an oblique-angled slamming wave acting on a rigid wall. In the present study the analytical approach is pursued based on a technique proposed by Shu (Proceedings of the International Conference on Applied Mathematics & Mathematical Physics, Sylhet, Bangladesh, 2000). A nonlinear theory in the context of potential flow is presented for determining accurately the free-surface profiles immediately after an oblique breaking wave impingement on the rigid vertical wall that suddenly starts from rest. The small-time expansion is taken as far as necessary to include the accelerating effect. The analytical solutions for the free-surface elevation are derived up to the third order. The results derived in this paper are of particular interest to the marine and offshore engineering industries, which will find the information useful for the design of ships, coastal and offshore.